ALPAMÍS DÁSTANÍ TILINDE «KÓZ» KONCEPTI MENEN KELGEN FRAZEOLOGIZIMLERDIŃ QOLLANÍLÍW ÓZGESHELIKLERI - Qutibaeva, A. (SCIENCE and SOCIETY, 2024)
The article is devoted to clarifying the differences in the use of somatic phraseology in the language of the epic “Alpamys”. The somatic phraseology of the epic was analyzed, the “Brief Phraseological Dictionary of the Karakalpak Language”, Zh. Eshbaeva.It was used. Theoretical view and opinios on the investigated topic of karakalpak and Kazakh scientists.